Проблеми та перспективи розвітку інноваційного потенціалу України - Долина, Ірина Володимирівна (НТУ "ХПІ", 2018)
Розглянуто основні складові сучасного стану інноваційної політики в Україні. Розглянуто складові інноваційного потенціалу, висвітлено основні проблеми державної підтримки розвитку інноваційного потенціалу, визначено основні напрями удосконалення регулюючого впливу держави на хід інноваційних процесів. На базі проаналізованих даних запропоновані напрями вдосконалення інноваційного розвитку України.

The main components of the current state of innovation policy in Ukraine are considered. The components of the innovation potential are considered, the main problems of state support for the development of innovation potential are highlighted, the main directions of improvement of the regulatory influence of the state on the course of innovation processes are determined. On the basis of the analyzed data, the directions of improvement of innovation development of Ukraine are offered. Over the past decades, the world has beenthe economy, especially developed countries, entered into a period of radical structural change associated with a significant increase in the role of high-techproduction, the development of which is determined by the wide introduction innovations in various spheres of economic (and, in general, social) life. This updates the issue innovation activity, which, as it turned out, is a prerequisite for construction effective economy, competitive in world markets.The transition of Ukraine to an innovative model of development is undeniable.
Problems of that perspective to the role of the innovative potential of Ukraine
Keywords: інновації; інноваційний розвиток; інноваційна політика; інноваційна продукція; державне регулювання; структура інноваційного потенціалу регіону; innovations; innovation development; innovative innovation; innovation policy; innovative products; state regulation; innovative potential; structure of innovative potential of the region